Pengaruh lama fermentasi terhadap pH, total asam, dan amonia ampas jus limbah sayur sebagai pakan - Sofia Sandi; Anggriawan Naidilah Tetra Pratama; Eli Sahara; Fitra Yosi; Meisji Liana Sari; Aptriansyah Susanda Nurdin (Jurnal Ilmu Peternakan Terapan, 2023)
Market vegetable waste is the remains of vegetables that are not sold, the result of weeding, or parts of vegetables that are not used for human consumption. This study aimed to determine the effect of fermentation time on nutrient composition, pH value, total acid, and ammonia of vegetable market waste juices. This study used a fermentation method with cabbage, mustard greens, carrots, and tomatoes as well as 8% salt fermentation additives and 7.7% molasses. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments consisted of P0 (fermentation time 0 days), P1 (fermentation time 6 days), P2 (fermentation time 12 days), and P3 (fermentation time 18 days). The observed variables included pH, total acid, and ammonia with the duration of fermentation of vegetable market waste juice. The results showed that the duration of fermentation of vegetable market waste juice had a significant effect (P<0.05) on pH, total acid, and ammonia. This research can be concluded that fermentation with a duration of 12 days can increase ammonia and total acid and reduce pH.